Bangladesh road to sustainable development : people's voice - People's Consultation on Sustainable Development: National Assessment Report for WSSD, Bangladesh (2002 : Forum of Environmental Journalists of Bangladesh); Chowdhury, Quamrul Islam; Forum of Environmental Journalists of Bangladesh (Dhaka : Forum of Environmental Journalists of Bangladesh, 2002)
Contributed articles presented at the People's Consultation on Sustainable Development: National Assessment Report for WSSD, Bangladesh conducted by Forum of Environmental Journalists of Bangladesh at six administrative divisional headquaters of Bangladesh between 19th Feb. to 10th March, 2002.
Keywords: Sustainable development -- Bangladesh -- Congresses